Two-dimensional computational modeling of the electrokinetic remediation of a copper-contaminated soil part ii: sensitivity analysis for a triangular soil field (2014)
The computer model described in the first paper of this series was used to perform a sensitivity analysis for the electrokinetic remediation of a triangular, copper-contaminated soil field in which one anode and two cathodes are placed in the vicinity of the triangle vertices. The input variables included the initial concentration of copper in the soil , the electrical potential applied between electrodes, and the absence or presence of wash water. The output variables included the cleanup efficiency and the fraction of copper eliminated from the soil fCu. Overall, the larger the electrical potential applied between electrodes, the shorter the time to achieve steady state. When no wash water is used, the cleanup efficiency may fluctuate over time before reaching steady state. When wash water is used, the final fCu obtained depends on the initial concentration of copper in the soil.